1978
DOI: 10.1051/jphys:01978003906059100
|View full text |Cite
|
Sign up to set email alerts
|

Effective hyperfine Hamiltonian in homonuclear diatomic molecules. Application to the B state of molecular iodine

Abstract: The effective hyperfine Hamiltonian is studied in the case of homonuclear diatomic molecules, using irreducible tensorial algebra. The second order perturbation terms due to the magnetic dipole and electric quadrupole Hamiltonian are calculated in a compact form. These calculations are applied to the B state of molecular iodine : the experimental values of the scalar and tensorial spin-spin coupling constants are interpreted. Moreover it is shown that the recently published magnetic octupole coupling value for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 10 publications
5
70
0
Order By: Relevance
“…[89] corrected errors in the Hamiltonian matrix of [88] and also in the forms adapted from [90]. An alternative formalism developed by [91], originally intended for application to the I 2 molecule, was applied to the b 3 Π u state of Na 2 by [37]. Later, [92], from observations of the 1 3 ∆ g state of Na 2 , and [93], from data on mixed A 1 Σ + u and b 3 Π u states of Na 2 , found that their observations could be explained almost entirely by the Fermi-contact parameter alone.…”
Section: A Hamiltonian Matrix Elementsmentioning
confidence: 99%
“…[89] corrected errors in the Hamiltonian matrix of [88] and also in the forms adapted from [90]. An alternative formalism developed by [91], originally intended for application to the I 2 molecule, was applied to the b 3 Π u state of Na 2 by [37]. Later, [92], from observations of the 1 3 ∆ g state of Na 2 , and [93], from data on mixed A 1 Σ + u and b 3 Π u states of Na 2 , found that their observations could be explained almost entirely by the Fermi-contact parameter alone.…”
Section: A Hamiltonian Matrix Elementsmentioning
confidence: 99%
“…A total of about 500 rotational lines were measured in the (5,1), (10,6) and (17,15) a The standard deviation of the last digits is given in parentheses…”
Section: Resultsmentioning
confidence: 99%
“…The numerical analysis was greatly facilitated by auto-QI~ (8) (10,6) band of the Ne(B--A) system is shown, as scanned with the resolution of [4] (left) and with the improved resolution of the present work (right). The bottom trace gives the frequency markers from a calibrated interferometer matic measurement of the peak wavelength of each hfs component.…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations